Analisis Kadar Abu Terhadap Kualitas Biochar Dari Cangkang Sawit - Amalia Syakinah Maharani Budaya; Aryo Sasmita; Edward HS (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Biochar can affect the microbial population and can act as an adsorbent in the soil. Palm shell potensially as a raw material for making biochar because it contains cellulose, hemicellose, and lignin. The purpose of this research was to compare the biochar characteristics of palm shells according to SNI. Biochar was pyrolyzed at 550oC for 30 minutes and activated using NaOH solution. Biochar from palm shells in this research has qualified for activated carbon based on SNI 06-3730-1995, with a ash content of 5,25%. Key words : Biochar, Palm shell, Ash